Ebola virus matrix protein VP40 triggers inflammatory responses linked to the ebolavirus virulence - Satoko Yamaoka; Zeineb M’Hamdi; Lin Wang; Vaille A. Swenson; Kristin L. McNally; Shao-Chia Lu; Reema Singh; Stephanie L. Saundh; Brady N. Zell; Sonja M. Best; Michael A. Barry; Angela L. Rasmussen; et al. (Proceedings of the National Academy of Sciences, 2026)
Uncontrolled systemic inflammatory responses are a critical pathological feature of fatal Ebola virus (EBOV) infection. While some inflammatory responses may originate from mononuclear phagocytes (MNPs), nonimmune cells vastly outnumber MNPs and may be an important source of inflammation. Here, we demonstrated that highly virulent EBOV induced a high and sustained pro-inflammatory response compared to less virulent ebolaviruses in non-MNPs through TLR4-independent NF-κB activation. We identified the EBOV matrix protein VP40 as a potent activator of NF-κB in non-MNPs, whose intrinsic inflammatory activation ability is higher than VP40 proteins from less virulent ebolaviruses. This suggests that VP40 is a virulence determinant inducing distinct degrees of pro-inflammatory responses among ebolaviruses. Mechanistically, VP40 activated the NF-κB signaling pathway, primarily via TNFR1 using a ligand-independent mechanism. These findings reveal mechanisms that may drive systemic inflammation and promote EBOV pathogenesis, suggesting potential therapeutic strategies to mitigate immune dysregulation in severe EBOV infections.